2020
DOI: 10.1534/g3.120.401215
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction and Selection for Fruit Traits in Winter Squash

Abstract: Improving fruit quality is an important but challenging breeding goal in winter squash. Squash breeding in general is resource-intensive, especially in terms of space, and the biology of squash makes it difficult to practice selection on both parents. These restrictions translate to smaller breeding populations and limited use of greenhouse generations, which in turn, limits genetic gain per breeding cycle and increases cycle length. Genomic selection is a promising technology for improving breeding efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…These results likely are due to the large index weight and substantial genetic gain for PHS. Gain in SI value and some component traits after calculating SI with GEBVs has been previously reported (Hernandez et al, 2020;Tiede & Smith, 2018).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These results likely are due to the large index weight and substantial genetic gain for PHS. Gain in SI value and some component traits after calculating SI with GEBVs has been previously reported (Hernandez et al, 2020;Tiede & Smith, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…Empirical experiments that evaluated realized genetic gain from GS in plants suggest GS and PS may perform similarly (Rutkoski et al., 2015; Sallam & Smith, 2016) but reduced cycle time in GS leads to greater gain per unit time. Use of a SI in GS may result in gain for component traits (Combs & Bernardo, 2013), index value (Massman et al., 2013), or both for positively (Hernandez et al., 2020) and negatively genetic correlated traits (Tiede & Smith, 2018). Prediction accuracy for SI value may be higher with GS than PS even if single trait accuracies are similar between the two methods (Heffner et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GWAS, marker data were used to calculate GEBVs, using best linear unbiased predictors (BLUPs) (Henderson 1963). First, the marker matrix used for estimation of kinship was thinned significantly: markers were thinned to a maximum density of one marker per 1 kb, with no missing data, resulting in 12,370 SNPs, with an average distance between SNPs of 36.55 kb; this marker density is sufficient to support maximal predictive ability, and thus was an appropriate base marker set for all subsequent analyses, as it allowed for each prediction accuracy-limiting variable to be evaluated individually.…”
Section: Genomic-estimated Breeding Valuesmentioning
confidence: 99%
“…Across all of these papers there was consensus that while the best specific GS modeling approach varied depending on the trait architecture, GS models in general were capable of predicting many agronomically important traits with a high enough accuracy compared to phenotypic selection to warrant incorporation into plant breeding programs. Since this review in 2017, the number of studies demonstrating the predictive capabilities of GS has increased and expanded from previously studied crops such as wheat (Arruda et al 2016;Belamkar et al 2018;Haile et al 2018;Lozada et al 2019), pea (Annicchiarico et al 2019, and alfalfa (Biazzi et al 2017), to a wider variety of plant species including sunflower (Dimitrijevic and Horn 2018), coffee (Sousa et al 2019), cassava (Wolfe et al 2017), strawberry (Gezan et al 2017), winter squash (Hernandez et al 2020), and cranberry (Covarrubias-Pazaran et al 2018). Cost-benefit analyses of incorporating GS into breeding programs were also discussed and indicated that GS can be substantially cheaper than phenotypic selection and brings the advantage that genotypes can be used for predicting multiple traits.…”
Section: Gs Transformed Plant Breedingmentioning
confidence: 99%